2010
DOI: 10.5194/nhess-10-2199-2010
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean hurricanes: large-scale environment and convective and precipitating areas from satellite microwave observations

Abstract: Abstract. Subsynoptic scale vortices that have been likened to tropical cyclones or polar lows (medicanes) are occasionally observed over the Mediterranean Sea. Generated over the sea, they are usually associated with strong winds and heavy precipitation and thus can be highly destructive in islands and costal areas. Only an accurate forecasting of such systems could mitigate these effects. However, at the moment, the predictability of these systems remains limited.Due to the scarcity of conventional observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 35 publications
(52 reference statements)
3
73
0
Order By: Relevance
“…Documented from both the observational (Moscatello et al, 2008b;Claud et al, 2010;Conte et al, 2011) and numerical (Moscatello et al, 2008a;Davolio et al, 2009;Miglietta et al, 2011) points of view, the role of the upper-level trough on the intensification of the storm has been evaluated for the first time.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Documented from both the observational (Moscatello et al, 2008b;Claud et al, 2010;Conte et al, 2011) and numerical (Moscatello et al, 2008a;Davolio et al, 2009;Miglietta et al, 2011) points of view, the role of the upper-level trough on the intensification of the storm has been evaluated for the first time.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This unique dataset combined with the strong intensity of the medicane motivated a number of studies using numerical experiments (Moscatello et al, 2008a;Davolio et al, 2009;Miglietta et al, 2011;Laviola et al, 2011) and satellite observations (Claud et al, 2010;Conte et al, 2011). The overview of the case given below is based on these previous studies.…”
Section: Overview Of the Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…According to Kleespies and Watts (2007), based on radiative transfer simulations for diverse atmospheric profiles, the brightness temperature bias between AMSU-B and MHS for channel 5 would be approximately 0.1 K, with a standard deviation of also approximately 0.1 K. A further evaluation, based on a larger sample, indicates that the differences between AMSU-B and MHS depend on the amount of water vapour in the atmosphere and range from −1 to 3 K (in the latter case when the atmosphere is very dry) (John et al, 2012). It has also been suggested that MHS could be more sensitive to convection than AMSU-B (Mo, 2006;Claud et al, 2010).…”
Section: Mhs/amsu-b Consistencymentioning
confidence: 99%
“…Claud et al, 2010). The forecast of the medicane was performed with the nonhydrostatic model Meso-NH (Lafore et al, 1998) using the two-way interactive gridnesting method with triply nested grids, with a horizontal grid spacing of 32, 8 and 2 km.…”
Section: Verification Of Meteorological Forecastsmentioning
confidence: 99%